Order and gelation of cellulose nanocrystal suspensions: an overview of some issues - Gray, Derek G. (Philosophical transactions of the Royal Society of London. Series A: Mathematical, physical, and engineering sciences, 2018)
Cellulose nanocrystals (CNCs) are polydisperse rod-shaped particles of crystalline cellulose I, typically prepared by sulfuric acid hydrolysis of natural cellulose fibres to give aqueous colloidal suspensions stabilized by sulfate half-ester groups. Sufficiently dilute suspensions are isotropic fluids, but as the concentration of CNC in water is increased, a critical concentration is reached where a spontaneously ordered phase is observed. The (equilibrium) phase separation of the ordered chiral nematic phase is in competition with a tendency of the CNC suspension to form a gel. Qualitatively, factors that reduce the stability of the CNC suspension favour the onset of gelation. The chiral nematic structure is preserved, at least partially, when the suspension dries. Solid chiral nematic films of cellulose are of interest for their optical and templating properties, but the preparation of the films requires improvement. The processes that govern the formation of solid chiral nematic films from CNC suspensions include phase separation, gelation and also the effects of shear on CNC orientation during evaporation. Some insight into these processes is provided by polarized light microscopy, which indicates that the relaxation of shear-induced orientation to give a chiral nematic structure may occur via an intermediate twist-bend state. This article is part of a discussion meeting issue 'New horizons for cellulose nanotechnology'.